Mission Santa Clara de Asis - Kessler, Friedolin Edward:::Creator:::::::::::: (Kessler, Friedolin Edward)
Linoleum cut print of Mission Santa Clara de Asis on paper, pasted on front of greeting card. In cursive at bottom of card, Mission Santa Clara de Asis by Friedolin Kessler.